Rapid synthesis of Au, Ag and Cu nanoparticles by DC arc-discharge for efficiency enhancement in polymer solar cells - Ekasiddh Wongrat (2018)
© 2017 Informa UK Limited, trading as Taylor & Francis Group In this work, Au, Ag and Cu nanoparticles (AuNPs, AgNPs and CuNPs) were rapidly synthesized by the DC arc-discharge technique. The applied electrical DC voltages of 225, 125 and 275 V were utilized to synthesize the AuNPs, AgNPs and CuNPs, respectively. The plasma arc-discharge was created from two identical metallic electrodes separated by a distance of 1 mm in liquid with a volume of 100 ml. The surface plasmon resonance peaks were analysed via UV–Visible spectroscopy and appeared at wavelengths of 578, 441 and 526 nm for CuNPs, AgNPs and AuNPs, respectively. The size distributions calculated from TEM images indicate mean particle sizes of 31, 73 and 99 nm for AuNPs, AgNPs and CuNPs, respectively. For solar cell application, the nanoparticles (NPs) introduced in the ZnO electron-transport layer and P3HT:PCBM active layer can improve the PCE of the devices with a significant increase in the short-circuit current density (J sc ). The PCE enhancement of polymer solar cells with NP incorporation may originate from the localized surface plasmon effect, which leads to light-harvesting enhancement due to the light-absorption and light-scattering mechanisms.